Penerapan Teknologi Tepat guna pada Budidaya dan Penanganan Pascapanen Tanaman Padi Organik - Salim, Iqbal; Diyah Yumeina; Abdul Azis; Mahmud Achmad; Sitti Nur Faridah; Husnul Mubarak; Syahrial Sabaniah; Khaeril Anwar Junaedi; Mursalim; Ahmad Munir; Salengke (Abdi Techno, 2026)
Rice is a major commodity as a source of carbohydrates for the Indonesian people. Efforts to increase rice production have been made by the government, but these have not been matched by optimal harvesting and post-harvest handling, resulting in high yield losses of nearly 10%. Data from the Central Statistics Agency (2024) shows that rice harvest losses reach 9.5% during harvesting and 4.8% during the post-harvest stage, which has the potential to reduce national grain production, currently recorded at around 65 million tonnes of grain. The Tompobulu sub-district, Bantaeng Regency, has around 1,000 hectares of rice fields at an altitude of ±500 metres above sea level with small plots and a terraced pattern. The main problems faced by organic rice farmers in this area are low knowledge of cultivation, organic fertiliser production, and good post-harvest handling. These conditions cause high yield losses, both quantitatively and qualitatively, which do not provide economic incentives for farmers to increase their income. Paddy with high moisture content is also easily damaged and increases yield losses. Appropriate and location-specific post-harvest handling is needed to reduce yield losses and improve grain quality. In areas with narrow land ownership and hilly topography, appropriate technology in the form of power threshers is a suitable solution, as modern harvesting equipment such as combine harvesters cannot operate effectively in terraced rice fields.